Une approche générationnelle des jeunes militants frontistes - Magali Boumaza (Temporalités)
This article applies a generational approach to study young people entering politics. It allows us to diffirentiate between the situation in the 19705 and today. During the 1970s, the young members of the FNJ (the French National Front Youth Section) mainly came from the declining middle class (their sociological profile was that of a shop employee’s son). They belonged to the post-Mai 1968 generation and were influenced by anticommunism, very strong at that time. From the point of view of the parry, they were the first generation of a very small group of extreme-right wingers in France. Their work as militants was to establish the party. Most of the young people entering the FNJ in the 1980s aimed to combat the movement led by « SOS Racisme ». Skinheads and hooligans reappeared on the scene. The French National Front was represented in Parliament in 1986 and in the 1990s, its influence grew, its members belonged to the working classes but the chief was part of the upper class. By examining a few examples of family socialization, we try to understand how the identity of NF youth was built and attempt to explain the split that took place in the party in 1998/1999.